The validity of the push band 2.0 on the reactive strength index assessment in drop jump - Montoro-Bombù, R.; de la Paz Arencibia, L.; Buzzichelli, C.; Miranda-Oliveira, P.; Fernandes, O.; Santos, A.; Rama, L. (Sensors, 2022)
This study aims to verify the validity of the Push Band 2.0 (PB2.0) device on the reactive strength index (RSI) measurement, using a force plate (FP) and an optical sensor device, OptoJump (OPT), as a reference. Twenty trained athletes performed 60 drop jump trials with a height box of 30 cm. A randomized repeated measures study was conducted during a single session using the PB2.0, the OPT, and the plate force manually synchronized to obtain RSI data for each jump. Validity was analyzed by contrasting three measures: the intra-class correlation coefficient (ICC), the Bland-Altman test, and R2 coefficient of determination. Bland-Altman analysis showed that RSI and FP for PB2.0 (media = -0.047; IC 93.34%) of all data were within the confidence interval, indicating a statistically reliable result. The RSI measured by the OPT and PB2.0 also provided similar values (media = -0.047). These data are identical to other validity measures (ICC and linear correlation) but differ in the R2 values. The explained variation of PB2.0 measures attained only 29.3% of the FP (R2 = 0.293) and 29.5% (R2 = 0.295) of the OPT assessment, showing a very low determination coefficient. The results of this study point to caution in the use of PB2.0 when measuring RSI in scientific research.